A Study Of Social Factors In Knowledge Management System Implementation - Poorsartep, Mohammad (2008)
This study addresses the social factors of KM implementation, specifically focusing on "System Acceptance" and "Trust" as independent variables and "Actual Usage" as dependant variable. Furthermore, knowledge chanpion, fear of criticism/misleading, and job security are the measures of trust whereas; management support, evaluation system, perceived relevance, and system accessibility as measures of system acceptance.